Застосування стратегічних інструментів під час управління бізнес-процесами аграрних підприємств - Горобець, Наталія Миколаївна; Gorobets, N.; Миргородська, Т. О.; Myrhorodska, T. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
У статті розглянуто застосування певних діагностичних методів стратегічного аналізу та планування виробничо-збутової діяльності сільськогосподарських підприємств. Доведено, що в сучасних кризових умовах господарювання процес формування системи ефективного функціонування аграрних підприємств передбачає використання нових підходів до оцінювання організаційно-економічних умов виробництва сільськогосподарської продукції, зміцнення конкурентних позицій агротоваровиробників, розробки збутової політики та кон'юнктури аграрного ринку в регіоні. Зроблено висновок про необхідність освоєння менеджерами агропідприємств стратегічних інструментів з метою розробки планів на підставі грунтовного аналізу впливу чинників зовнішнього та внутрішнього середовища підприємства. Обгрунтовано доцільність розробки управлінських рішень агроменеджерами на підставі застосування інструментів стратегічного аналізу, а саме: SWOT-аналіз та SNW-аналіз. Запропоновано стратегічний підхід до процесу управління сільськогосподарськими підприємствами, що дає можливість своєчасно та якісно реагувати на зміни в середовищі їх функціонування, формувати конкурентні переваги, які в довгостроковому періоді забезпечать стабільну конкурентоспроможність та досягнення стратегічних цілей. The article deals with the application of certain diagnostic methods of strategic analysis and planning of production and marketing activities of agricultural enterprises. Noted the main reasons for the ineffective implementation of strategies in the activity of enterprises. It is proved that in the current economic crisis, the process of forming a system of efficient functioning of agricultural enterprises involves the use of new approaches to the evaluation of organizational and economic conditions of agricultural production, strengthening the competitive position of agricultural producers, development of marketing policies and conditions of the agricultural market in the region. The conclusion is made about the necessity of development by the managers of agricultural enterprises of strategic tools for the development of plans on the basis of a thorough analysis of the influence of factors of the external and internal environment of the enterprise. It is noted that the use of strategic analysis tools in the study of the internal environment of the organization is aimed at identifying factors that shape long-term profitability and are under the direct control of the head of the enterprise. The expediency of development of management decisions by agrarian managers based on the use of strategic analysis tools such as SWOT analysis and SNW analysis is substantiated. It is established that SWOT analysis allows to systematize problematic situations, to better understand the structure of resources, to develop strategies. With the help of SNW analysis as a tool for assessing the potential of the enterprise, it is possible to estimate the resource, economic, production, marketing, management potential. It is established that such diagnostics of the internal environment reveals a number of system problems that exist in the object under study. A strategic approach to the process of managing agricultural enterprises is offered, which enables timely and qualitative reaction to changes in their environment, forming competitive advantages that will ensure stable competitiveness and achievement of strategic goals in the long term.
Strategic management of business processes in the system for sale of the agricultural products
Н. М. Горобець ORCID ID: 0000B0001B5032B2903 ; Т. О. Миргородська ORCID ID: 0000B0001B6179B0489
Keywords: управління; management; стратегія; strategу; стратегічні інструменти; strategic tools; стратегічний аналіз; strategic analysis; SWOT-аналіз; SWOT-analysis; SNW-аналіз; SNW-analysis; бізнес-процес; business process; аграрні підприємства; agricultural enterprises